Report of The Working Group on Agriculture - Planning Commission (Planning Commission, 1972)
Later, on November 30, 1971, Dr. Nilakantha Rath, Professor of Economics, Gokhale Institute of Politics and Economics, Poona was appointed as an additional member of the Working Group. On transfer of Shri S. M. Murshed from the Department of Agriculture, Shri K. K. Bhatnagar, Deputy Secretary (Manpower), Department of Agriculture was nominated as a member in his place. Dr. A. K. Dutt, Director of Agriculture, Government of West Bengal could attend only one of the meetings. Miss F. K. Wadia, Joint Director, Committee on Unemployment was nominated as Secretary to the Working Group.
Government of India Committee on Unemployment
Government of India Committee on Unemployment